2015
DOI: 10.1177/0961203315611496
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance evaluation of paediatric patients with systemic lupus erythematosus and cardiac symptoms

Abstract: CMR identifies heart involvement in a significant percentage of SLE children with cardiac symptoms and normal routine noninvasive evaluation.The incidence of heart disease is lower in SLE children compared with SLE adults.Predominance of myocarditis and myocardial infarction is observed in SLE children and SLE adults, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…4,12,37 Anti-SSA/SSB antibodies have been found to be associated with cardiac involvement in cSLE 37,38 and anti-malarial therapy protects from future SLE-associated cardiac diseases. 39 …”
Section: Cardiac Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,12,37 Anti-SSA/SSB antibodies have been found to be associated with cardiac involvement in cSLE 37,38 and anti-malarial therapy protects from future SLE-associated cardiac diseases. 39 …”
Section: Cardiac Manifestationsmentioning
confidence: 99%
“…43 Indeed, CMRI was able to identify LM in cSLE patients with cardiac symptoms and normal ECHO. 38 Cardiac enzymes may be normal in LM and troponin levels are more commonly elevated than CK-MB levels. 44 LM may be associated with skeletal myositis.…”
Section: Myocarditismentioning
confidence: 99%
“…Cardiac involvement, the leading cause of death in patients with systemic lupus erythematosus (SLE) , has received increasing attention over the past decade . Several investigators have suggested that the incidence of cardiac impairment ranges from 31% to 70% .…”
mentioning
confidence: 99%
“…To date, methods for detecting SLE‐induced cardiac involvement are not ideal, due to the lack of a reliable examination technique. Negative findings on electrocardiography or echocardiography cannot exclude the presence of severe cardiac disease in patients with SLE . Ideal diagnostic tools for elucidating myocardial injury and follow‐up are needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation